Photo-triggered release of 5-fluorouracil from a MOF drug delivery vehicle. Issue 55 (21st June 2018) - Roth Stefaniak, Kristina; Epley, Charity C.; Novak, Joshua J.; McAndrew, Margaret L.; Cornell, Hannah D.; Zhu, Jie; McDaniel, Dylan K.; Davis, Jennifer L.; Allen, Irving C.; Morris, Amanda J.; Grove, Tijana Z.
Abstract : A nano metal–organic-framework (nanoMOF) was employed as a first-of-its kind drug delivery vehicle (DDV) for the photo-controlled release of therapeutics with simultaneous breakdown of the carrier into small molecules. Abstract : A nano metal–organic-framework (nanoMOF) was employed as a first-of-its kind drug delivery vehicle (DDV) for the photo-controlled release of therapeutics with simultaneous breakdown of the carrier into small molecules.